Monitoring Application for Student Activity Units Administration Data of Nurul Jadid University Based on Android - M Syafiih; Nadiyah; Matlubul Khairi (Department of Informatics, Faculty of Science and Technology, UIN Prof. K.H. Saifuddin Zuhri, Purbalingga, Indonesia, 2024)
Nurul Jadid University (UNUJA) at Probolinggo, Indonesia, is one of the universities located in Karanganyar, Paiton District, Probolinggo Regency, which is based in Pesantren, as a place for students who want to gain knowledge not only in the religious field- but also technology and health. Administrative data monitoring activities from 17 Student Activity Units owned by Nurul Jadid University are still run manually or face-to-face directly between the student affairs section and the head of the student affairs section starts monitoring from submission of decision letters, budgets, work programs, proposals, and activity reports of each student activity units. Several problems arise in this way; the busyness of students with a tight lecture schedule causes a slow process of depositing files and others, impacting the predetermined time- Therefore, an application is needed to monitor administrative data at Nurul Jadid University. The RAD method was chosen in this study to achieve the expected goals. An Android-based student activity unit (SAU) of Nurul Jadid University of administration data monitoring application has been produced.